Innovation in Public Relations and Marketing for Islamic Higher Education Branding: Developing a Pesantren-Based Holistic Marketing Model - Tri Joko Susanto; Imam Makruf; Mudofir (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
The increasing competition in higher education requires institutions to strengthen their branding through effective public relations and marketing strategies. Islamic higher education institutions rooted in pesantren traditions face distinctive challenges in integrating religious values, community trust, and modern management practices within institutional branding. This study aims to examine innovations in public relations and marketing and to develop a conceptual model at STAI and Ma’had Aly Idrisiyyah Tasikmalaya, Indonesia. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and document analysis involving institutional leaders, lecturers, students, and alumni. The data were analyzed to identify patterns of marketing practices, communication strategies, and institutional branding approaches. The findings indicate that marketing practices are gradually shifting from conventional promotional activities toward more strategic communication functions, although they have not yet been fully integrated into institutional management systems. Institutional branding is strongly influenced by spiritual leadership, social networks, and community trust, while the use of digital communication platforms remains limited. Based on these findings, this study proposes a pesantren-based holistic marketing model that integrates managerial, cultural, and spiritual dimensions in institutional branding. This model contributes to the development of marketing and public relations theory in Islamic higher education and provides practical insights for strengthening institutional competitiveness through values-based branding strategies.